Leibniz Type AQ-Functional Equation in Non-Archimedian Fuzzy Normed Spaces - M. Arunkumar; John. M. Rassias; G. Ganapathy (International Journal of Mathematics And its Applications, 2016)
In this paper, we establish the generalized Ulam - Hyers stability of a Leibniz type Additive-Quadratic functional equation \begin{align*} f(x-t)+f(y-t)+f(z-t)&= 3f\left(\frac{x+y+z}{3}-t\right)+f\left(\frac{2x-y-z}{3}\right) \\ &+f\left(\frac{-x+2y-z}{3}\right) +f\left(\frac{-x-y+2z}{3}\right) \end{align*} in Non-Archimedian Fuzzy normed space, using direct and fixed point methods.